2014
DOI: 10.1111/tpj.12434
|View full text |Cite
|
Sign up to set email alerts
|

Extensive amplification of the E2F transcription factor binding sites by transposons during evolution of Brassica species

Abstract: SUMMARYTransposable elements (TEs) are major players in genome evolution. The effects of their movement vary from gene knockouts to more subtle effects such as changes in gene expression. It has recently been shown that TEs may contain transcription factor binding sites (TFBSs), and it has been proposed that they may rewire new genes into existing transcriptional networks. However, little is known about the dynamics of this process and its effect on transcription factor binding. Here we show that TEs have exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 42 publications
2
50
0
Order By: Relevance
“…Remarkably, also using less stringent criteria to detect E2F-like elements () no additional putative E2F sites could be found in any of the intergenic regions upstream of the AtDRTS genes. Interestingly, the E2F-like element upstream of AtDRTS3 is located in the middle of a transposon-like element and a recent study has reported that E2F sites are relatively common in plant transposable elements [41]. …”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, also using less stringent criteria to detect E2F-like elements () no additional putative E2F sites could be found in any of the intergenic regions upstream of the AtDRTS genes. Interestingly, the E2F-like element upstream of AtDRTS3 is located in the middle of a transposon-like element and a recent study has reported that E2F sites are relatively common in plant transposable elements [41]. …”
Section: Resultsmentioning
confidence: 99%
“…The release of transcriptional and post-transcriptional silencing of TEs can lead to bursts of TE activity, rapidly generating new genetic diversity (Vitte et al, 2014). TEs may carry regulatory information such as promoters and transcription factor binding sites, and their mobilization may lead to the creation or expansion of gene regulatory networks (Hénaff et al, 2014; Bolger et al, 2014; Ito et al, 2011; Makarevitch et al, 2015). Furthermore, the transposase enzymes required and encoded by TEs have frequently been domesticated and repurposed as endogenous proteins, such as the DAYSLEEPER gene in Arabidopsis, derived from a hAT transposase enzyme (Bundock and Hooykaas, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In animal cells this is the case for OCT4 and NANOG, Sox2, c-Myc, and CTCF, among others (Bourque et al, 2008; Kunarso et al, 2010; Lynch et al, 2011; Schmidt et al, 2012; Jacques et al, 2013) and recently for E2F in several Brassicaceae , including Arabidopsis (Henaff et al, 2014). Thus, up to 85% of the sequences that fit the E2F consensus sequence in Arabidopsis are amplified in TEs and ChIP experiments show that they bind E2Fa in vivo , indicating that the overall availability of E2F can be affected by E2F binding to TEs.…”
Section: The G1 Transcriptional Wave (Mid G1)mentioning
confidence: 88%
“…Thus, up to 85% of the sequences that fit the E2F consensus sequence in Arabidopsis are amplified in TEs and ChIP experiments show that they bind E2Fa in vivo , indicating that the overall availability of E2F can be affected by E2F binding to TEs. These data suggest that TEs located in the proximity of gene promoters may directly participate in their expression level and those in other locations affect the effective nuclear concentration of E2F and its transcriptional network (Henaff et al, 2014). …”
Section: The G1 Transcriptional Wave (Mid G1)mentioning
confidence: 99%